CV Juridical Review Of Legal Protection For Aspected Customers - Imam Wahyudi; Hono Sejati (Publikasi Indonesia, 2023)
Efforts to guarantee legal protection and certainty as well as to avoid conflicts of interest as a result of using banking services, especially in banking credit services that carry out economic functions through actions that are suspected of being a misuse of circumstances and can result in losses for consumers. The study uses an analytical method with an empirical juridical approach or legal sociology, privileges and commitments contained in Article 4 of the Shopper Security Act, as follows: 1) The option to solace, security, and wellbeing in consuming merchandise or potentially benefits; 2) The option to pick products and additionally benefits and acquire said products as well as administrations under the swapping scale and the circumstances and certifications guaranteed; 3) Right to right, self-evident and fair data in regards to the circumstances and certifications of merchandise or potentially benefits; 4) The option to have their perspectives and protests found out about the merchandise as well as administrations utilized; 5) The option to get legitimate backing, insurance, and endeavors to determine purchaser insurance debates; 6) The option to get direction and shopper schooling; 8) The option to be dealt with or served appropriately and truly and not biased; h. The option to get pay, pay, or potentially repayment if the products as well as administrations got are not by the arrangement or not as they ought to be; 9) The rights are managed in the arrangements of different guidelines and rules.